Animals Are Not Ours (No, Really, They're Not) : an Evangelical Animal Liberation Theology. - King, Sarah Withrow (Cambridge : The Lutterworth Press, 2016)
A robust challenge to traditional evangelical assumptions about humanity's ""dominion"" over the animal world, arguing for a biblical ethic of animal liberation.
Introduction to Part Three19: Don't Eat Them; 20: Don't Beat Them (or Pay People Who Do); 21: Your Animal Companions; 22: PETA's Community Animal Project (and How You Can Help Animals in Your Own Community); 23: Buying Cruelty Free; 24: Public Policies; 25: Frequently Asked Questions; Epilogue; Glossary; Bibliography; Back cover.
Print version record.
Master record variable field(s) change: 050
Keywords: Animal welfare -- Religious aspects -- Christianity; Animals -- Religious aspects -- Christianity; Animal rights -- Religious aspects -- Christianity; RELIGION -- Christian Theology -- Ethics; NATURE -- Animal Rights; Animal rights -- Religious aspects -- Christianity; Animal welfare -- Religious aspects -- Christianity; Animals -- Religious aspects -- Christianity; Electronic books